2013
DOI: 10.1017/s1355617713000064
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Executive Deficits in People with Parkinson's Disease

Abstract: Executive functioning is frequently impaired among people with Parkinson's disease (PD). Little is known about awareness of executive functioning, in the sense of being able to accurately appraise functioning or performance, in people with PD, or about whether awareness is particularly affected in those who have impaired executive functioning. This study explored awareness of executive functioning at the levels of evaluative judgment (comparison of self- and informant ratings of executive functioning), and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 61 publications
7
52
0
Order By: Relevance
“…For example, in PD patients, it has been recently shown that self-ratings of executive functioning, particularly in those with executive dysfunction, were higher and less accurate than informant ratings [16]. Similar to AD and FTD patients, those with PD irrespective of the presence of global cognitive impairment have impaired metamemory for episodic information [22, 23, 61].…”
Section: Summary Of Findings: Self-awareness and Metacognitive Accuramentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in PD patients, it has been recently shown that self-ratings of executive functioning, particularly in those with executive dysfunction, were higher and less accurate than informant ratings [16]. Similar to AD and FTD patients, those with PD irrespective of the presence of global cognitive impairment have impaired metamemory for episodic information [22, 23, 61].…”
Section: Summary Of Findings: Self-awareness and Metacognitive Accuramentioning
confidence: 99%
“…Historically, the vast majority of metacognitive research has examined the phenomenon of self-reflection in the healthy brain, and young adults in particular, [11, 12]. In recent years, metacognition has also advanced to study older adults [2, 13], especially those with clinical deficits and across a range of clinical populations [14-16]. Not only does metacognitive work provide the foundation for understanding how the self operates, but it informs wide ranging practical issues such as the development of optimal educational strategies, and the variables to be considered when evaluating or relying on eyewitness testimony in forensic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, impairments in self‐appraisal ability (inappropriately positive or negative self‐appraisal) have been noted in previous reports among MCI subjects . In this regard, there is limited information on the self‐appraisal ability of PD‐MCI subjects, although efforts are beginning to be made in reporting impaired accuracy of PD patient self‐reports of dyskinesias and cognitive deficits . Additionally, there is a significant literature on the factors (e.g., memory performance, depression) that relate to anosognosia in dementia and lack of accurate patient self‐appraisal in MCI, but little is known about the nature of factors impacting patient self‐appraisal ability among PD‐MCI subjects.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest the need to attend to deficits in memory and executive function, as subtle disruption in these areas increases the likelihood that a patient is not capable of giving consent. Indeed, people with PD MCI may also have reduced awareness of executive function impairment, potentially compromising safety and judgment in naturalistic settings 15 . In such cases, study precautions should be considered, including a structured assessment of capacity and asking the patient to designate a study partner.…”
Section: Discussionmentioning
confidence: 99%